A COMPARATIVE STUDY BETWEEN THE USE OF VSS (VOCABULARY SELF-COLLECTION STRATEGY) AND SVES (STEPHENS VOCABULARY ELABORATION STRATEGY) ON STUDENTS’ VOCABULARY MASTERY AT SMPN I BANTAN IN BENGKALIS REGENCY - Nurbi, Leni Nurpitasari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The main purpose of this research was to find out the significant difference on students’ vocabulary mastery between using VSS (Vocabulary Self-Collection Strategy) and SVES (Stephens Vocabulary Elaboration Strategy) on students’ vocabulary mastery at SMPN I Bantan in Bengkalis Regency. The design of this research was a comparative study with a comparative quasi-experimental design. This research used multiple choice test and questionnaire. The data were analyzed by using Paired Sample T-test, Independent Sample T-test and Effect Size. The results of this research were; first, the significant effect of using VSS on students’ vocabulary mastery. The researcher found the significant 0.00 < 0.05. Second, the researcher also found the significant effect of using SVES on students’ vocabulary mastery. The researcher found the significant 0.00 < 0.05. Last, the researcher found the significant difference in vocabulary mastery between students taught by using VSS and SVES. The significant value was 0.022 < 0.05. In conclusion, VSS is more effective than SVES to improve students’ vocabulary mastery. The mean gain score of VSS was higher than the mean gain score of SVESS (18.48 > 15.87). Key Word: VSS (Vocabulary Self-Collection Strategy), SVES (Stephens Vocabulary Elaboration Strategy), Vocabulary Mastery.